Age and sex differences in niche use at molt and its effect on plumage coloration characteristics in a bird. Issue 3 (27th July 2018) - Pagani-Núñez, Emilio; Barnett, Craig R A; Senar, Juan Carlos
Abstract: Bird plumage is often very colorful and can communicate the quality of the bearer to conspecifics. These plumage-based signals of quality are composed of multiple pigments (e.g., melanin and carotenoids). Therefore, sex and age classes, which often show marked differences in plumage coloration, may have different dietary needs for the different plumage components and this might promote preferences for different dietary niches at different molting stages. However, no study has addressed the role that changes in niche use play in the expression of multiple component plumage signals in birds. We used stable isotope analysis to test the hypothesis that niche use is related to age and sex and to differently cultured plumage patches, yellow carotenoid-based and black melanin-based, in great tits Parus major . We recorded high niche overlap between plumage patches, although δ 15 N was higher in black than yellow plumage. Niche overlap was relatively low for age classes and relatively high for sex classes, and age classes showed a contrasting pattern of niche overlap between carotenoid- and melanin-based plumages. Moreover, δ 13 C, but not δ 15 N, had a significant negative relationship with carotenoid-based plumage, which was only apparent in juveniles. Taken together, our results demonstrate that niche use had a moderate influence on plumage coloration characteristics of great tit individuals, mostly associated with δ 13 C rather than with δ 15 N and with age rather than with sex. Therefore, our study is significant because it confirms the relevance of niche use during ornament production in free-living birds.